Deformation-induced phosphorescence shift in a 2D elastically flexible organic single crystal: role of chalcogen-centered weak interactions. Issue 35 (19th August 2022) - Bhandary, Subhrajyoti; Van Deun, Rik; Kaczmarek, Anna M.; Van Hecke, Kristof
Abstract : In response to macroscopic elastical bending, single crystals of dual emissive dibenzothiophene depict a significant blue shift (∼20 nm) of RTP emission when compared to their pristine crystals (straight and naturally bent). Abstract : Mechanically responsive organic luminescent crystals are one of the promising choices of materials for flexible photonic devices. However, the change in phosphorescence emission as a function of the flexibility of a crystal has never been reported. Our current findings demonstrate two-dimensional (2D) and one-dimensional (1D) macroscopic elastic deformability, under mechanical stress, in elastically flexible single crystals of dibenzothiophene, and its brominated derivative, respectively. Unlike the presence of dual fluorescence (FL) and room temperature phosphorescence (RTP) in dibenzothiophene single crystals, the derivative was found to show only RTP. Interestingly, upon elastic deformation, single crystals of the dual emissive dibenzothiophene show a noticeable blue shift (∼20 nm) of RTP emission when compared to their pristine crystals (straight and naturally bent). However, their FL peaks remain nearly unchanged irrespective of the crystal deformation. A hierarchy of structure-elastic functionality to RTP modulation has been quantitatively mapped by rationalizing the role of chalcogen-involved weak interactions.